2015
DOI: 10.1002/adfm.201501707
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Facile Formation of P3HT Organogels via Spin Coating: Tuning Functional Properties of Organic Electronic Thin Films

Abstract: Poly(3-hexyl thiophene) (P3HT) is widely regarded as the benchmark polymer when studying the physics of conjugated polymers used in organic electronic devices. P3HT can self-assemble via π-π stacking of its backbone, leading to an assembly and growth of P3HT fi brils into 3D percolating organogels. These structures are capable of bridging the electrodes, providing multiple pathways for charge transport throughout the active layer. Here, a novel set of conditions is identifi ed and discussed for P3HT organogel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Over the relatively brief timescale of spin-coating, a polymer film is created through the quick removal of solvent via fluid motion and evaporation. 14 desired morphologies and architectures. 15,16,17 There exists a wide range of proposed pathways through which some of the more common conjugated polymers aggregate during the gelation process including percolation 18 and phase separation.…”
Section: Introductionmentioning
confidence: 99%
“…Over the relatively brief timescale of spin-coating, a polymer film is created through the quick removal of solvent via fluid motion and evaporation. 14 desired morphologies and architectures. 15,16,17 There exists a wide range of proposed pathways through which some of the more common conjugated polymers aggregate during the gelation process including percolation 18 and phase separation.…”
Section: Introductionmentioning
confidence: 99%
“…Note that α-6T was reported as an excellent templating material for both ambipolar OFETs and light-emitting FETs [ 34 , 35 ]; P3HT always acted as a model conjugated polymer due to its high hole mobility, solution processibility, and potential to self-assemble during processing [ 36 ]. To further verify the abovementioned assumptions, the organic semiconductors of α-6T and P3HT were used as active layers to fabricate OFETs containing a PVA dielectric layer.…”
Section: Resultsmentioning
confidence: 99%
“…[166] Dadmun and co-workers reported a study on the effect of solvent and solution concentration on the formation of poly(3-hexylthiophene) organogels. [167] A minimal initial solution concentration and boiling point of the solvent were determined to be necessary for gelation to occur. They reported that with increasing boiling point of the solvent, larger organogel networks can be formed due to a longer formation time.…”
Section: Organogelsmentioning
confidence: 99%